The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1415-52732011000500010
|View full text |Cite
|
Sign up to set email alerts
|

Pode o peso ao nascer influenciar o estado nutricional, os níveis de atividade física e a aptidão física relacionada à saúde de crianças e jovens?

Abstract: A aptidão física relacionada à saúde é definida como um conjunto de atributos fisiológicos que o indivíduo apresenta para o desempenho de atividades físicas diárias sem fadiga excessiva. Sabe-se que fatores como atividade física e estado nutricional influenciam diretamente os níveis de aptidão física. Entretanto, o aporte adequado de nutrientes nos períodos iniciais da vida é determinante para o crescimento e o desenvolvimento de órgãos e de sistemas. O peso ao nascer está relacionado ao desenvolvimento intrau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A systematic review approaching such large literature indicated a higher risk of preterm birth and low weight among mothers of single births with low gestational weight gain 29 . Hence, it is worth mentioning that the consequences of low birth weight and height deficit in childhood can go beyond due to the negative repercussions on health at long term [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review approaching such large literature indicated a higher risk of preterm birth and low weight among mothers of single births with low gestational weight gain 29 . Hence, it is worth mentioning that the consequences of low birth weight and height deficit in childhood can go beyond due to the negative repercussions on health at long term [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%